Chitosan nanocomposites with graphene-based filler - Maraschin, Thuany Garcia (2019)
This study evaluates the properties of chitosan (CS) membranes modified with different percentages (0.5%, 3%, and 5% w/w) of a graphene-based material. Graphene oxide (GO) and reduced graphene oxide (RGO) were obtained by the chemical exfoliation of graphite and thermal reduction. Then, they were characterized by electrical conductivity measurements, FESEM, XRD, AFM, and Raman spectroscopy. The composites’ morphology was evaluated by FESEM. The degree of swelling over a 48 h period and mass loss behavior in phosphate-buffered saline solution for up to 70 days were also studied. The hydrophilicity of the CS and CS/graphene nanocomposites was examined by water contact angle. The graphene materials showed small stacks (6–8 sheets) with low defect density and nanoscale thickness (1.3–5.9 nm). The dispersion of the graphene material in the CS matrix significantly decreased the degree of swelling (460%) but did not modify the hydrolytic degradation process and the hydrophilicity of membranes.